The Economics of Corporate Reorganization - Buchanan, N. S. (Quarterly Journal of Economics, 1939)
I. The meaning of “failure” and “reorganization,” 29. — II. The economics of reorganization. Liquidation value of the assets: specialization, 32; separability, 33; costs of liquidation, 34. — Value in reorganization, 35. — Uncertainty of computations, 37. — Readjustment of claims: the “absolute priority rule,” 38. — Difficulties: conflicting valuations, 40; inducing new investment, 41. — III. Comparison of procedures. The major problems to be solved: deciding upon reorganization or liquidation, 44; procuring new capital, 46; dealing with dissenting minorities, 47; ensuring independent and disinterested review, 48; keeping costs down, 49.